2016
DOI: 10.1007/s11249-016-0707-6
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary and Quaternary Ammonium-Phosphate Ionic Liquids as Lubricant Additives

Abstract: In this work, we investigated the feasibility of five quaternary (aprotic) and four tertiary (protic) ammonium ionic liquids (ILs) with an identical organophosphate anion as lubricant anti-wear additives. Viscosity, oil solubility, thermal stability and corrosivity of the candidate ILs were characterized and correlated to the molecular structure. The protic group exhibits higher oil solubility than the aprotic group, and longer alkyl chains seem to provide better oil solubility and higher thermal stability. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 44 publications
1
60
0
1
Order By: Relevance
“…3a and 4c ), or transform to the amorphous bulk tribofilm layer by mechanochemical reactions. Wear particles may also be incorporated inside the tribofilm through mechanical mixing, which was previously seen in severe boundary lubrication with excessive wear debris 9 , 14 . Since the material removal in steel-steel contact is moderate, the inclusion of nanoparticles within the tribofilm was at minimum presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3a and 4c ), or transform to the amorphous bulk tribofilm layer by mechanochemical reactions. Wear particles may also be incorporated inside the tribofilm through mechanical mixing, which was previously seen in severe boundary lubrication with excessive wear debris 9 , 14 . Since the material removal in steel-steel contact is moderate, the inclusion of nanoparticles within the tribofilm was at minimum presence.…”
Section: Discussionmentioning
confidence: 99%
“…Since the surface morphology, material composition, and contact condition all change rapidly, various approaches have been used to study the interface phenomena: on-line monitoring 1 4 , periodic oil analysis 5 , 6 , and off-line worn surface analysis 7 . Oil-miscible ionic liquids (ILs) have recently been reported as novel lubricant anti-wear (AW) additives providing effective wear reduction that is widely attributed to the formation of a protective tribofilm on the contact area 8 14 . At the same phosphorus concentration, ILs offer potentially superior wear protection 8 with less adverse impact on the exhaust emission catalysts 15 compared with the conventional zinc dialkyldithiophosphates (ZDDPs).…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature ionic liquids (ILs) have demonstrated great potential for many chemical and engineering fields, including tribology and lubrication [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Although most research efforts during the first decade of the 21st century were focused on the use of ILs as neat lubricants, our research group reported the use of ILs as lubricant additives since our first works on the subject [14][15][16].…”
Section: Room-temperature Ionic Liquid Lubricants and Additivesmentioning
confidence: 99%
“…Although most research efforts during the first decade of the 21st century were focused on the use of ILs as neat lubricants, our research group reported the use of ILs as lubricant additives since our first works on the subject [14][15][16]. The use of ILs as lubricant additives is one of the main topics of interest at the present moment [13,[19][20][21][22].Some important research lines which are being pursued at present are the substitution of the conventional aprotic halogen-derived ILs by more environmentally friendly halogen-free protic or aprotic ILs, and the combination of ILs with nanophases to create synergistic effects with enhanced friction-reducing, antiwear, and surface protective performances [18]. …”
mentioning
confidence: 99%
“…Since the first report in 2001 proposing the use of ILs for lubrication, [14] a number of studies have been published on the lubrication mechanism of ILs, most of which focused on imidazolium-, [22,25] phosphonium-, [26,27] or phosphate-based ILs. [28] Studies at the nanoscale have ascribed the lubrication mechanism of ILs to their adsorption and confinement between smooth surfaces, in absence of any mechano-chemical reactions. [4,29,30] The confined ions resist being "squeezed out" when surfaces are compressed, thus resulting in a film that prevents direct contact between the two surfaces.…”
Section: Introductionmentioning
confidence: 99%